Design of a Web-Based Notary Deed Archiving System Application at the Office of Notary Ani Yaniatin Pitaloka, S.H. - Eryan Ahmad Firdaus; Topik Hidayat; Jonson Manurung; Ajeng Hidayati; Muhammad Azhar Prabukusumo (NUANSA INFORMATIKA, 2025)
A notarial deed is a legal document that has strong evidentiary power in court and in various legal transactions. Based on Law No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 on Notary Position (Notary Law), this law regulates the duties, responsibilities, and authority of notaries, including provisions on the archiving and security of documents handled by notaries. Therefore, it is important for notary institutions, lawyers, and various related parties to manage these notarial deeds carefully and effectively, one of which is by paying attention to the archiving of notarial deeds. The archiving of notarial deeds is an important practice in the legal world involving the storage, maintenance, and recording of notarial deed documents that govern legal agreements, property transactions, and other legal actions. By designing a web-based archiving application system, the goal of addressing the risk of damage or loss of physical documents is effectively achieved. The implementation of digital storage methods reduces the likelihood of physical documents being damaged or lost. Document accessibility is also enhanced by the presence of search and digital storage features. Application design steps, such as needs analysis, use case diagrams, activity diagrams, and interface design, provide a comprehensive overview of the desired features and system workflow. This design ensures that user needs are met and the application is easy to use.